The role of peer social support on family psychological resilience in caring for Chronic Kidney Disease patients receiving hemodialysis - Lilik Supriati; Muhammad Sunarto; Ikhda Ulya; Muhammad Rodli; Rendi Yoga Saputra; Renny Nova; Nur Hidaayah (Healthcare in Low-resource Settings, 2024)
Chronic Kidney Disease (CKD) is a disease that necessitates continuous Hemodialysis (HD) therapy, and families, as primary caregivers in Indonesia, play a crucial role in caring for CKD patients. However, HD therapy places a significant burden not only on patients but also on their families, requiring fostering family psychological resilience to mitigate such a burden. Although peer social support is an important external factor in chronic disease, it is still underdeveloped. Therefore, this study aimed to explore the correlation between peer social support and family psychological resilience in caring for CKD patients receiving HD. This cross-sectional study used purposive sampling, engaging 134 families serving as caregivers for patients receiving HD therapy. The Berlin Social Support Scales (BSSS) and The Walsh Family Resilience Questionnaire (WFRQ) were adopted as instruments, and data were analyzed using univariate and Spearman tests. The majority of families reported high levels of peer social support (75,37%), predominantly originating from other members facing similar challenges related to caring for CKD patients. Additionally, a significant relationship was observed between peer social support and family psychological resilience (p-value<0.05), showing that higher levels of peer support corresponded to higher family resilience. In conclusion, there was a strong correlation between peer social support and family resilience in the context of caring for CKD patients. Healthcare professionals should integrate social support intervention by establishing social groups to enhance family resilience.